Management of Court Records: Functional Requirements Framework for Electronic Recordkeeping System / Rusnah Johare, Nurussobah Hussin and Adnan Jamaludin - Johare, Rusnah; Hussin, Nurussobah; Jamaludin, Adnan (2011)
This paper highlights the need for electronic court records management in the Judiciary. The aim of the study is to develop a functional requirements framework for electronic recordkeeping system in the Superior Courts of Malaysia. This paper discusses the results of the data analysis of the various international and national best practices of functional requirements for electronic records management and courts management across selected organizations in Australia, Canada, UK, US, Singapore and Malaysia. The framework development for the execution phase are based on three steps i.e. identify, analyze and development. The method of the data collection is document analysis. Findings of the analysis shows that all of the civil records management functions that have been identified comply with the functional requirements of electronic records management. With regard to the functional requirements specific to recordkeeping system of the courts, there were no comprehensive functional requirements developed which integrate the functions of electronic records management in the functional requirements of the courts. Therefore, the researchers have to analyze sixteen functional requirements to successfully identify the functions of electronic records management and civil cases/records management that are relevant to the study. It is hoped that the development of the framework requirements will contribute to automated recordkeeping functionality, enhance the ability to support auditing activities, improve the court of appeal business processes and assist to ensure good governance through good recordkeeping. Keywords: Civil records; Superior Courts; Electronic records; Recordkeeping; Functional Requirements